The effect of screw spacing on the Profiled Steel Sheet Dry Board (PSSDB) with foamed concrete infill floor panel stiffness - Nor Asmaq, Baharom (2015)
Profiled steel sheeting dry board is the new technology that had been used in civil engineering field as slab, roof and wall structure. Profiled steel sheeting dry board panel is a composite structural system consisting of profiled steel sheet (PSS) connected to dry board by simply mechanical connector. It had been used in United Kingdom to substitute the usage of timber formwork on the construction site. Previous researchers were done to determine fire resistance performance and strength of the panel by using different type of methods and material such as dryboard, profiled steel sheeting (PSS), concrete as infill and screw size. This experiment was conducted to determine the stiffness performance on the PSSDB panel when foamed concrete is used as an infill and the result was compared with the PSSDB floor panel without infill. It was also conducted to determine the effect of the screw spacing toward stiffness performance of the floor panel system. This experiment used three (3) samples with differences screw spacing that are Sample 1(100mm), Sample 2 (150mm) and Sample 3(200mm). Compressive strength cube test was done to obtain the strength of the foamed concrete used. Another experiment is bending test, conducted by using Magnus Frame and Apparatus 30 tonnes and attached with transducer to get the data of deflection. The Whiffle-Tree method was use simulate uniformly distribution load to the whole panel system. All the data collected and analyzed to show the performance of the panels system in stiffness. The result shows that the stiffness for Sample 1 is 192 kNm2/m, Sample 2 is 168 kNm2/m and Sample 3 is 162 kNm2/m. It shows that when the screw spacing used increase, the stiffness of the PSSDB floor panel system increased. This is because of the profiled steel sheeting and dry board was stick together firmly by the screw.